EXPLORING STUDENTS' SELF-DIRECTED AND COLLABORATIVE LEARNING IN RESEARCH COURSES: A COMPARISON OF IN-PERSON AND WRITTEN-RESPONSE INTERVIEWING. - Yuchun Zhou; Min Lun Wu; Yuqing Liu (Journal of Ethnographic & Qualitative Research)
Traditional teaching approaches in research methods courses demotivate students, hindering their ability to learn and apply research concepts in practical settings. Instructors who are devoted to employing active learning pedagogy in teaching research courses have observed favorable outcomes. However, a dearth of literature has focused on students' perceptions and evaluation of active learning pedagogy. This study explores how students perceive active learning approaches via in-person and writtenresponse interviews. Eighteen participants volunteered and self-selected one of the interview forms. In addition to exploring students' perspectives on active learning pedagogy, we conducted a comparison of those interviewing modes. Our analysis revealed that regardless of interview type, participants provided similar results. In-person interviews generated more information segments; however, the segments from written-response interviews provided more informative meaning. Combining all data, we developed three themes and 29 codes about students' perceptions of active learning pedagogy. We found that students valued self-exploration as well as interactive activities that promoted deep learning and knowledge transfer. Based on the results, we provide practical recommendations for how instructors can design active learning-based research courses to facilitate students in active and self-regulated learning.